East Timor new future, hidden past (United Kingdom : Journeyman Pictures, 2003)
East Timor's new governmentt is striving to promote reconciliation with Indonesia and militias who slaughtered innocents in the bloody vote for independence
Keywords: East Timor -- Politics and government